The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/jvim.16160
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome and prognostic factors in dogs with B‐cell chronic lymphocytic leukemia: A retrospective study

Abstract: Background: B-cell chronic lymphocytic leukemia (BCLL) in dogs generally is considered an indolent disease, but previous studies indicate a wide range in survival times.Objectives: We hypothesized that BCLL has a heterogeneous clinical course, similar to chronic lymphocytic leukemia in humans. We aimed to assess presentation and outcome in dogs with BCLL and evaluate the prognostic relevance of clinical and flow cytometric factors. Animals: One hundred and twenty-one dogs with BCLL diagnosed by flow cytometry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(48 citation statements)
references
References 40 publications
4
41
3
Order By: Relevance
“…12,25 However, dogs with lymphocytosis in this study appeared to have a much more aggressive clinical course with an OS of 133 days, as compared to a MST of 300 to 480 days 12,24 for dogs with BCLL, despite a majority of dogs having a lymphocytosis of <60 000/μL which was associated with an improved prognosis for dogs with BCLL. 12 MCL, another subtype comprised of small to intermediate-sized B-cells, primarily affects the spleen in dogs and nodal MCL appears quite uncommon. 3,20,21 We hypothesized that Ki67 expression, which is a marker of cellular proliferation, would be a useful prognostic factor for small cell B-cell lymphoma.…”
Section: Clinical Outcome and Survival Analysiscontrasting
confidence: 53%
See 2 more Smart Citations
“…12,25 However, dogs with lymphocytosis in this study appeared to have a much more aggressive clinical course with an OS of 133 days, as compared to a MST of 300 to 480 days 12,24 for dogs with BCLL, despite a majority of dogs having a lymphocytosis of <60 000/μL which was associated with an improved prognosis for dogs with BCLL. 12 MCL, another subtype comprised of small to intermediate-sized B-cells, primarily affects the spleen in dogs and nodal MCL appears quite uncommon. 3,20,21 We hypothesized that Ki67 expression, which is a marker of cellular proliferation, would be a useful prognostic factor for small cell B-cell lymphoma.…”
Section: Clinical Outcome and Survival Analysiscontrasting
confidence: 53%
“…12,24 It is possible dogs with BCLL were included in this study as a subset of BCLL cases can have nodal involvement. 12,25 However, dogs with lymphocytosis in this study appeared to have a much more aggressive clinical course with an OS of 133 days, as compared to a MST of 300 to 480 days 12,24 for dogs with BCLL, despite a majority of dogs having a lymphocytosis of <60 000/μL which was associated with an improved prognosis for dogs with BCLL. 12 MCL, another subtype comprised of small to intermediate-sized B-cells, primarily affects the spleen in dogs and nodal MCL appears quite uncommon.…”
Section: Clinical Outcome and Survival Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated median RFP and lymphoma related survival time for all dogs were 414 days (95% confidence interval (CI), range 228–600 days) and 442 days (95% CI, range 236–648 days), respectively, in a study published by Pioggi et al [ 49 ]. Another study reported 121 cases treated by chemotherapy, with a median survival time (MST) of 300 days (range 1–1644 days) [ 50 ]. In yet another study, median RFP was 196 days (range 22–1656 days) and OST was 292 days (range 40–2246 days) of dogs receiving CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisolone) based protocols [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many bulldogs were started on prednisone and chlorambucil with a presumptive diagnosis of chronic lymphocytic leukaemia based on blood film review. In humans and dogs, B‐cell chronic lymphocytic leukaemia (B‐CLL) is considered an indolent disease, in which many patients with early‐stage disease can be monitored without therapy 1,16–19 . Polyclonal B‐cell lymphocytosis of English bulldogs (PBLEB), a recently described non‐neoplastic disease of predominantly young, male English bulldogs is also indolent and characterized by an expansion of small mature B lymphocytes without peripheral lymph node involvement 13 .…”
Section: Discussionmentioning
confidence: 99%